Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1039/c4cc09439e
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochromic luminescence and aggregation induced emission for a metal-free β-diketone

Abstract: Reversible mechanochromic luminescence (ML) is known for difluoroboron β-diketonates (BF2bdks). Here, we report ML for the methoxy-substituted dinaphthoylmethane (dnmOMe) ligand even without coordination to boron. In addition, dnmOMe shows solvatochromism and aggregation-induced emission (AIE). Diketone thin films showed high contrast emission when smeared, and rapid recovery of the pre-smeared state at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 60 publications
3
46
0
Order By: Relevance
“…1,2 Difluoroboron β-diketonate (BF 2 bdk) complexes are of particular interest due to their impressive emission properties and the facile synthesis of β-diketonates via Claisen condensation from a variety of commercially available ketones and esters. 1,3-7 Desirable properties of BF 2 bdks include high extinction coefficients, 8-10 high quantum yields, 8-10 two-photon absorption cross-sections, 8,11 a range of emission colors in solution and the solid state, 10,12 solvatochromism, 4 and the ability to impart significant intramolecular charge transfer (ICT) character in unsymmetrical analogues. 13 Previously we reported the unique mechanochromic luminescent (ML) properties 6,7,12,14,15 of BF 2 bdk dyes as well as their ability to act as dual-emissive ratiometric oxygen sensors in polymer media.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Difluoroboron β-diketonate (BF 2 bdk) complexes are of particular interest due to their impressive emission properties and the facile synthesis of β-diketonates via Claisen condensation from a variety of commercially available ketones and esters. 1,3-7 Desirable properties of BF 2 bdks include high extinction coefficients, 8-10 high quantum yields, 8-10 two-photon absorption cross-sections, 8,11 a range of emission colors in solution and the solid state, 10,12 solvatochromism, 4 and the ability to impart significant intramolecular charge transfer (ICT) character in unsymmetrical analogues. 13 Previously we reported the unique mechanochromic luminescent (ML) properties 6,7,12,14,15 of BF 2 bdk dyes as well as their ability to act as dual-emissive ratiometric oxygen sensors in polymer media.…”
Section: Introductionmentioning
confidence: 99%
“…These resultsi ndicated thatt he fluorescencec olor change upon grinding was due to the crystalline-to-amorphous transformation. [37][38][39] The changes in morphologyb etween the original sample (crystalline) and ground sample (amorphous) were also apparent from the SEM images ( Figure S4 in the Supporting Information). After the ground sample was fumigated by EA vapor,t he XRD reflection peaks reappeared along with the recoveryoft he fluorescence.…”
Section: Stimulus-responsive Fluorescent Behaviors Of Solid-state Ndhpmentioning
confidence: 82%
“…These reflection peaks were largely absent from the pattern of the ground sample owing to its amorphous nature. These results indicated that the fluorescence color change upon grinding was due to the crystalline‐to‐amorphous transformation . The changes in morphology between the original sample (crystalline) and ground sample (amorphous) were also apparent from the SEM images (Figure S4 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The bdk ligandsw ith different cyclic amine substituents were synthesized using Claisen condensation as previously reported. [27] The BF 2 bdk dyes werep reparedb yb oronation of the ligands using boron trifluoride diethyle therate. [28] For optical property measurements, stock solutions of the bdk ligands and BF 2 bdk dyes were prepared by dissolving compounds in CH 2 Cl 2 .A ppropriate volumeso fs tock solution were then diluted to obtain standard 10 À5 m CH 2 Cl 2 solutions.…”
Section: Synthesis and Optical Propertiesmentioning
confidence: 99%